ECB strategy: Best practice and new frontiers - Sebastian Dullien; Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
The ECB's strategy of inflation targeting as currently practiced requires only minor adjustments to allow the ECB to best provide price stability and support the EU's general economic policies. The key to inflation targeting is a distinct and symmetric inflation target that serves as a benchmark for private-sector expectations and a central bank that is held accountable and transparently justifies its policy actions. As one of only two macroeconomic policies, the remit of monetary policy is not limited to its primary objective of price stability. Preventing or reversing labor market hysteresis should factor into monetary policy decisions as should climate change considerations. In contrast, the lack of owner-occupied housing services in the HICP is often overstated and might lead to the potentially detrimental inclusion of asset prices in the inflation measure. A political solution to the euro area's safe asset problem - outside the ECB's remit - would facilitate monetary policy, increase the overall resilience of the euro area and bolster the international role of the euro.
Keywords: 330; Geldpolitik; Inflationssteuerung; Wirtschaftspolitisches Ziel; Zentralbank; Eurozone